2014
DOI: 10.1088/0004-637x/786/1/16
|View full text |Cite
|
Sign up to set email alerts
|

NuSTAR J033202–2746.8: DIRECT CONSTRAINTS ON THE COMPTON REFLECTION IN A HEAVILY OBSCURED QUASAR AT z ≈ 2

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 106 publications
3
27
0
Order By: Relevance
“…The rest-frame 10-40 keV energy range roughly corresponds to the observed 8-24 keV NuSTAR band (where we perform detection) for z ≈ 0.3-1 (where the bulk of our sample lies) and is becoming the standard for extragalactic NuSTAR surveys (e.g., Alexander et al 2013;Del Moro et al 2014).…”
Section: Kev -mentioning
confidence: 72%
See 1 more Smart Citation
“…The rest-frame 10-40 keV energy range roughly corresponds to the observed 8-24 keV NuSTAR band (where we perform detection) for z ≈ 0.3-1 (where the bulk of our sample lies) and is becoming the standard for extragalactic NuSTAR surveys (e.g., Alexander et al 2013;Del Moro et al 2014).…”
Section: Kev -mentioning
confidence: 72%
“…X-ray spectral analysis of the NuSTAR sources is underway (see Alexander et al 2013;Del Moro et al 2014, A. Del Moro et al 2016, in preparation and L. Zappacosta et al 2016. For this study, we adopt the statistical approach used by A15.…”
Section: Kev -mentioning
confidence: 99%
“…The extent and strength of reflection in such sources, especially those with L * luminosities and at z 1 that make a large contribution to the CXB flux, is still a matter of debate (e.g. Vasudevan et al 2013;Del Moro et al 2014). Indeed, the CXB can be reproduced with a wide variety of models that assume different X-ray spectral models for the constituent AGNs, as well as different XLFs, NH distributions, and-perhaps most crucially-Comptonthick fractions (e.g.…”
Section: The Nh Distribution the Fraction Of Compton-thick Agns And mentioning
confidence: 99%
“…For example, changing L i,X threshold values by±50% translates into a 3-5 factor difference in median and upper bound R values. A z=2 quasar selected in the NuSTAR-ECDF-S field and analyzed in Del Moro et al (2014) is reported in the plots as the starred data point. This source shows a low degree of reflection, comparable to the luminous/obscured AGN in our sample.…”
Section: The Reflection Componentmentioning
confidence: 99%
“…Lansbury et al (2017a) identified three similar sources at z 0.1 < that have even higher obscuration in the NuSTAR serendipitous survey. At high redshift, Del Moro et al (2014) presented the detection of a heavily absorbed (N 6 10 H 23 =´cm 2 -) quasar at z = 2. The redshift range and the luminosities probed by the NuSTAR extragalactic survey program are well-matched to CXB population-synthesis models, in terms of characterization of the AGN high-energy spectral shape and of the dominant obscured populations contributing to the CXB.…”
Section: Introductionmentioning
confidence: 99%